An Introduction to Philosophy - Payne, Russ W. (Open textbook library., 2023)
The goal of this text is to present philosophy to newcomers as a living discipline with historical roots. While a few early chapters are historically organized, the goal in the historical chapters is to trace a developmental progression of thought that introduces basic philosophical methods and frames issues that remain relevant today. Later chapters are topically organized. These include philosophy of science and philosophy of mind, areas where philosophy has shown dramatic recent progress. This text concludes with four chapters on ethics, broadly construed. Traditional theories of right action is covered in a third of these. Students are first invited first to think about what is good for themselves and their relationships in a chapter of love and happiness. Next a few meta-ethical issues are considered; namely, whether they are moral truths and if so what makes them so. The end of the ethics sequence addresses social justice, what it is for one's community to be good. Our sphere of concern expands progressively through these chapters. Our inquiry recapitulates the course of development into moral maturity. Over the course of the text, the author has tried to outline the continuity of thought that leads from the historical roots of philosophy to a few of the diverse areas of inquiry that continue to make significant contributions to our understanding of ourselves and the world we live in.